Potential For Financing New Renewable Energy Solar Energy in Supporting Green Banking - Rahman, Yuwanda; Syarifudin, Faiz; Mardiyah, Meicicho; Sukresna, I Made (LifeSciFi, 2024)
Indonesia, with great potential in the use of solar energy due to its position at the equator, has significant opportunities in developing the renewable energy sector. This journal will explore the potential of solar energy financing in supporting green banking initiatives in Indonesia. Through an analysis of government policies, economic benefits and environmental impacts, this journal and journal highlights how solar energy can contribute to sustainable development and carbon emission reduction. The banking sector has a key role in providing various financing products for solar energy projects. These products include green investment loans, People's Business Loans for small and medium enterprises and the issuance of green bonds. Solar energy financing is not only profitable from an environmental perspective but also offers portfolio diversification and improved bank image. The journal identifies key challenges in the implementation of solar energy financing, such as high initial costs and lack of public understanding as well as offering solutions such as education and attractive financing schemes. By harnessing the potential of solar energy, banks in Indonesia can support the transition to a green economy and contribute to climate change mitigation.